The Silent Voice of the Cushite Woman: Race, Identity, and Power in Numbers 12 - Putrawan, Bobby Kurnia (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This article explores the biblical narrative of the Cushite woman in Numbers 12, focusing on the intersections of race, gender, and power within the ancient Israelite context. The background of this study lies in the marginalization of non-Israelite women in biblical texts, particularly the Cushite woman, whose identity and role have been largely overlooked. The purpose of this article is to investigate how her silence and the criticism from Moses' siblings, Miriam and Aaron, reflect broader themes of racial and gender-based exclusion. Using a qualitative analysis of the biblical text, this study examines the implications of her marginalization within the power structures of ancient Israel, as well as the racial prejudices embedded in the narrative. The results suggest that the Cushite woman’s silence, while often interpreted as subjugation, can also be viewed as a form of subtle resistance against the patriarchal and racial systems at play. Contribution: This article contributes to a more nuanced understanding of how marginalized figures were portrayed in the Bible, and it reflects on the ongoing relevance of these themes in modern discussions of race, gender, and authority.